Study of some physicochemical properties of clay from the Belek deposit of the Sokuluk district (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents the results of a study of some physicochemical properties of clay from the Belek deposit in the Sokuluk district. Moisture, plasticity, chemical and mineral composition were determined. IR spectral analysis was performed. The results show that the Belek clay contains a high amount of aluminosilicates and has sufficient plasticity, making it suitable for use in the construction and ceramic industries.
Keywords: clay, Belek deposit, physicochemical properties, plasticity, porosity, IR spectroscopy